ESTIMASI HASIL PRODUKSI TBS DI PTPN IV REGIONAL 4 DENGAN METODE INTERPOLASI POLINOM - ERJANDSA, PUSPA HANAYA LATIFAH; ROZI, SYAMSYIDA (E-Jurnal Matematika; Vol 13 No 4 (2024)DO - 10.24843/MTK.2024.v13.i04.p468, 2024)
The study aimed to provide an accurate prediction model to enhance decision-making and operational efficiency in the palm oil industry. The data in this research included the cultivated land area and Fresh Fruit Bunch (FFB) production records for the year 2023. Newton Polynomial Interpolation is a mathematical technique to estimate unknown values between data. In this research, it was applied to derive production estimates across varying land sizes. The result demonstrated a consistent relationship between land area and production output, as illustrated through linear scatter plots. Production estimates for land areas ranging from 20 hectares to 850 hectares yielded 385,996.381 kg and 21,159,940.984 kg FFB. This research concludes that as the land area increases, FFB production shows a propotional upward trend, supporting the utility of Newton’s interpolation method in agricultural forecasting. The findings contribute significantly to the company’s planning processes and reinforce the importance of integrating mathematical models in optimizing resource utilization and achieving production targets.